Some Biological Characteristics of the Daysciaena albida (Cuvier 1830), on Largest Brackish Water Lagoon of India - Karna, SK; Panda, S (Ecoprint: An International Journal of Ecology, 2015)
An attempt to study length-weight relationship (LWR), condition factor and reproductive aspects of Daysciaena albida was done in Chilika lagoon over one year. The fish specimens for the biological study were collected from landing centers of central and northern sector during pre-monsoon, monsoon and post-monsoon seasons. The LWR from total length and body weight were computed both by sex and seasons. The equations found from the relationships were y=0.010x2.992 for male, y=0.010x2.998 for female and y=0.010x2.996 as unsexed specimens. The highest condition factor (K) value was recorded during monsoon (1.42±0.08) followed by post-monsoon (1.4±0.09) and the lowest (0.92±0.11) during pre-monsoon seasons. The mean condition factor was registered as 1.06±0.09 in all the seasons of unsexed specimens. Among sex, males registered slightly higher K value than females. For reproductive study, maturation stages, gonad somatic index (GSI) and gastro somatic index (GaSI) were analyzed seasonally. Considering maturation stages highest maturation stages (stages 4 to 7) obtained during pre-monsoon season (in both sexes) which are considered as matured conditions for fish. The highest GSI was registered during pre-monsoon followed by postmonsoon and the lowest was during monsoon season among both the sexes. The GaSI value was lowest during pre-monsoon among males and gradually increased during monsoon and postmonsoon. But in case of female, lowest value was during monsoon and again increased afterwards and was highest in pre-monsoon. ECOPRINT 21: 15-21, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11900